Effect of side-chain functionality on the organic field-effect transistor performance of oligo(p-phenylenevinylene) derivatives - Chini, Mrinmoy Kumar; Chatterjee, Shyambo (Journal of Applied Polymer Science, 2017)
In order to observe the effects of the substitution of electronegative flourine with aromatic groups in oligo(p-phenylenevinylene) compounds on their packing, morphology, and charge carrier mobility, we have synthesized napthol-substituted oligo(p-phenylenevinylene) compounds and examined their solubility, redox properties, thin film morphologies, and charge carrier properties. To date, very few examples of conjugated oligomers bearing napthol side groups have been reported in the literature. After annealing at 150 degrees C, the mobility of S1, S2, and S3 was 4.0x10(-2) cm(2) V-1 s(-1), 1.2x10(-2) cm(2) V-1 s(-1), and 2.6x10(-3) cm(2) V-1 s(-1), respectively. (c) 2017 Wiley Periodicals, Inc.